KUNCI SUKSES MIGRASI DATA SALDO AWAL BARANG MILIK NEGARA PADA SISTEM SAKTI - Iskandar, Iskandar; Marsono, Agung Triyanto Joko (Ultimaccounting Jurnal Ilmu Akuntansi, 2024)
Abstract—This research aims to determine the key factors for successful migration of state-owned asset data from the previous system to the SAKTI system. This research paradigm is a qualitative type which is aimed at gaining insight through exploring the complexity of phenomena in data migration programmes, in the form of initial balances of state-owned asset data from existing applications to SAKTI. Data collection was carried out through literature study and observation. The research results showed that the key factors that determine the success of migrating state-owned asset data to SAKTI are mechanisms including centralized data migration, phasing the migration process, correcting data anomalies in existing applications, increasing human resource capacity related to the data migration process, assisting users with the migration process, reconciliation, providing follow-up application features for data anomalies and normalization residues and technical instructions, providing migration monitoring tools, and increasing IT infrastructure capacity/bandwidth. The research results are useful as lessons learned about organizational aspects in the data migration process, both in the public/government and private domains. Keywords: Data Migration; State-Owned Asset; Fixed Assets; Critical Success Factors; Data Anomaly; Initial Balance